Peran Edukasi KKN dalam Literasi Perbankan Syariah dan Menabung Dini desa Ndeskati Kecamatan Naman Teran Kabupaten Karo - Yuli Andini; Nuraini Nuraini; Nislah Khoirunnisa Nst; Yusuf Hadijaya (Jurnal Pengabdian Masyarakat, 2025)
The Community Service Program (KKN) was implemented at SDN Ndeskati, Naman Teran District, Karo Regency, with the aim of improving Islam ic financial literacy and fostering a saving habit from an early age. This activity was motivated by the low level of Islamic financial literacy in rural areas, where elementary school students generally have limited knowledge of both the basic principles of Islamic banking and the importance of saving. The methods included interactive counseling, educational games, and saving simulations through class piggy banks. Evaluation was carried out using simple pre-test and post-test assessments. The results showed a significant improvement: students who regularly saved increased from 20% to 70%, students who understood the benefits of saving rose from 25% to 85%, and students who were able to identify basic principles of Islamic banking improved from 15% to 78%. In addition, teachers committed to continuing the school saving program, while parents expressed support for encouraging their children to save, with some showing interest in opening Islamic savings accounts. Thus, this KKN activity proved effective in enhancing Islamic financial literacy and cultivating a saving culture among elementary school students in rural areas.